Design and evaluation of oral nanoemulsion drug delivery system of mebudipine. (23rd July 2016) - Khani, Samira; Keyhanfar, Fariborz; Amani, Amir
Abstract: A nanoemulsion drug delivery system was developed to increase the oral bioavailability of mebudipine as a calcium channel blocker with very low bioavailability profile. The impact of nano-formulation on the pharmacokinetic parameters of mebudipine in rats was investigated. Nanoemulsion formulations containing ethyl oleate, Tween 80, Span 80, polyethylene glycol 400, ethanol and deionized water were prepared using probe sonicator. The optimum formulation was evaluated for physicochemical properties, such as particle size, morphology and stability. The particle size of optimum formulation was 22.8 ± 4.0 nm. Based on the results of this study, the relative bioavailability of mebudipine nanoemulsion was enhanced by about 2.6-, 2.0- and 1.9-fold, respectively, compared with suspension, ethyl oleate solution and micellar solution. In conclusion, nanoemulsion is an interesting option for the delivery of poorly water soluble molecules, such as mebudipine.